Development of Android-Based Interactive Media as a Learning Tool for Informatics Education in Junior High School - Idul Fitrianti; Anas Arfandi; Andi Muhammad Irfan (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This study aimed to develop and evaluate Android-based interactive media as a learning tool for Informatics education in junior high schools, addressing the continued reliance on conventional print media that limits active student engagement with computational-thinking and digital-literacy competencies. A Research and Development (R&D) design was employed, synthesizing the Plomp, ADDIE, and Borg and Gall models into five stages: investigation, design, development, analysis and revision, and dissemination. The media was validated by two subject-matter experts and two media experts, then trialed with students and teachers from two public junior high schools in Makassar City, Indonesia, culminating in a large-group trial involving 60 students and 12 teachers. Data were analyzed descriptively for validity and practicality and inferentially using a paired-sample t-test for effectiveness. The media achieved a very valid rating from subject-matter experts (82%) and media experts (85%), and very practical ratings across the individual (81%), small-group (87%), large-group (87%), and teacher-response (90%) trials. Learning outcomes improved significantly from pre-test (M = 58.92, SD = 19.03) to post-test (M = 85.83, SD = 11.76), t (59) = -10.91, p < .001. These findings indicate that Android-based interactive media integrating instructional videos, self-paced navigation, automated-feedback quizzes, and educational games is a valid, practical, and effective tool for improving Informatics learning outcomes at the junior secondary level. The study contributes an empirically validated, game-enhanced mobile-learning model that can inform the design of similar digital learning media in resource-constrained secondary-school settings.